War horse - Spielberg, Steven, 1946-; Irvine, Jeremy; Watson, Emily, 1967-; Mullan, Peter; Williams, John, 1932-; Morpurgo, Michael; Stafford, Nick, 1959- (Burbank, CA : Touchstone Home Entertainment, 2012)
Albert Narracott enlists to serve in World War I after his beloved horse Joey is sold to the cavalry.
Based on the novel by Michael Morpurgo and the stage play by Nick Stafford.
Originally released as a motion picture in 2011.
Features: War horse : the look.
Camera, Janusz Kaminski ; editor, Michael Kahn ; music, John Williams ; production designer, Rick Carter.
Jeremy Irvine, Emily Watson, Peter Mullan, David Thewlis, Niels Arestrup, Tom Hiddleston, Benedict Cumberbatch, Toby Kebbell.
MPAA rating: PG-13.
Keywords: Morpurgo, Michael -- Film adaptations; Stafford, Nick -- Film adaptations; War horses -- Drama; World War, 1914-1918 -- Drama; Animal films; Fiction films; Based on the book; Feature films; Historical films